1966
DOI: 10.1002/ange.19660782016
|View full text |Cite
|
Sign up to set email alerts
|

Bis‐cyclooctatetraen‐titan und Tris‐cyclooctatetraen‐dititan

Abstract: Uns gelang erstmals eine Synthese fliichtiger ternarer Verbindungen des Phosphors, Schwefels und Wasserstoffs. Dazu wurden die Gase HzS + PH3 oder D2S + PD3 oder CH3SH + PH3 im Molverhaltnis 1 : 1 gemischt und bei einer Stromungsgeschwindigkeit von 0,5 mmol/niin und ca. 0,l Torr einer elektrodenlosen Glimmentladung (900 V bei 90 mA und 27 MHz) ausgesetzt und die Produkte bei -196°C ausgefroren; der Urnsatz betrug 0,5-1,0 %. Die unmittelbar hinter der Entladungszone entnommenen Gase wurden entweder direkt in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1966
1966
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Cyclooctatetraene is also well-known to act as a bridging ligand, e.g. in [COTNd 2 THF][Nd (COT) 2 ] [13] and (COT) 3 Ti 2 [14]. IR data indicate that association takes place through the eight-membered ring.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclooctatetraene is also well-known to act as a bridging ligand, e.g. in [COTNd 2 THF][Nd (COT) 2 ] [13] and (COT) 3 Ti 2 [14]. IR data indicate that association takes place through the eight-membered ring.…”
Section: Resultsmentioning
confidence: 99%
“…The dianion of cyclooctatetraene has been used successfully to prepare COT complexes of primarily the early transition metals (e.g., Ti(»;8-C8H8)(? ;4-C8H8), ref 9), metals in the actinide series (e.g., U(t;8-CsH8)2, ref lc), and metals in the iron triad (e.g., Ru-(bicyclo[2.2.1 ]hepta-2,5-diene)(7j6-C8H8), ref 10). This technique is cleaner and more predictable than that employing reducing agents such as aluminum alkyls in the presence of COT and seemed particularly suitable for preparation of Nb and Ta COT complexes.…”
Section: Resultsmentioning
confidence: 99%
“…These methods are found to predict correctly the experimentally observed structures for the known Ti [10], V [17], and Fe [18] derivatives. New structures are predicted for the (C 8 H 8 ) 2 M derivatives of the other metals, namely Cr, Mn, Co, and Ni.…”
Section: Introductionmentioning
confidence: 56%
“…Among the first row transition metals a bis(cyclooctatetraene) titanium derivative, (h 8 -C 8 H 8 )Ti(h 4 -C 8 H 8 ), was reported in 1966 as a product from reactions of titanium alkoxides with aluminum alkyls in the presence of excess cyclooctatetraene [10]. A subsequent X-ray structural study [11] showed that one of the C 8 H 8 rings is fully bonded as an octahapto ligand, but the other C 8 H 8 is bonded through only four of the eight carbon atoms as a 1,2,3,4-tetrahapto ligand similar to the cyclooctatetraene ligand [12] in (h 4 -C 8 H 8 )Fe(CO) 3 , discovered a few years earlier by three independent research groups ( Fig.…”
Section: Introductionmentioning
confidence: 99%